PENERAPAN MEDIA ROSETTA STONE DALAM MENGAJAR KOSAKATA BAHASA INGGRIS MELALUI METODE DYNAMIC IMMERSION TERHADAP SISWA SMP 3 NEGERI 3 PADANGSIDIMPUAN - Nursaima Harahap; Siti Meutia Sari; Yulia Rizki Ramadhani (Linguistik : Jurnal Bahasa dan Sastra, 2019)
This research aims to improve the vocabulary of students' English vocabulary and student learning outcomes using Rosetta Stone through Dynamic Immersion media. The Dynamic Immersion is an audiovisual method without translation, so it is hoped that the brains of students will immediately become accustomed to associating English words with visual images.After the instrument is declared valid and has a high level of reliability, the next step is to provide pre-test and post-test to both groups. The test given is a learning achievement test in the form of an objective test in the form of multiple-choice related to the vocabulary theme of singular and plural vocabulary which is done by students of the control class and the experimental class.Hypothesis testing is done to find out whether there is a significant influence on the Rosetta Stone media through the dynamic immersion method to the learning outcomes of Grade VII students of SMP Negeri 3 Padangsidimpuan. Hypothesis testing in this study was conducted using a test analysis with analysis using the SPSS statistical program. The results of calculations from the t-test were 4.93 with Df = na + nb - 2, Df = 68, a significance level of 5%, then t-table = 1.99. So the result of the t-test is 4.93> 1.99. So, the t-test is bigger than the t-table. Based on the results, it means that there are significant differences in the post-test scores between the experimental group and the control group.Based on the decision-making basis of the independent sample t-test in this study, it can be concluded that the implementation of Rosetta Stone useful as a medium in teaching vocabulary mastery of seventh-grade students of SMPN 3 Padangsidimpuan. Keywords: vocabulary, rosetta stone, dynamic immersion